PEMANFAATAN MIKROORGANISME DALAM BIOREMEDIASI SENYAWA PENCEMAR - Ahmad Shafwan S. Pulungan (Universitas Negeri Medan, 2015)
Bioremediation is a process that involves living creatures in the remediation or degradation of pollutant compounds. The ability of living creatures is demonstrated by the activity of plants and microorganisms. Microorganisms have potential as bioremediation agents. The ability of bioremediation by microorganisms turned out to be done enzymatically involving enzyme activities of some types of microorganisms that work together to overhaul chains pollutant substances into compounds that are better for the environment. These enzymes, among others, oksireduktase, oxygenation, lipase and cellulase. Bioremediation process requires a long time, due to the need for the process of adaptation in a given environment. Key words. Bioremediation, Microorganisms, Enzyme, Degradation